Modeling and simulation of high redundancy actuator for fault-tolerance. (2018) - Manohar, G. Arun; Vasu, V.; Srikanth, K.
Abstract: The High Redundancy Actuator (HRA) deals with the intrinsic fault-tolerance actuation by having a large number of small actuation elements coupled in series and parallel configuration. Each actuation element is a linear Electromechanical Actuator (EMA) and these actuators work collectively to form a single HRA. The mathematical modeling and simulation of a HRA having nine actuation elements in 3×3 series-in-parallel configuration are discussed in the present work. The performance of single actuation element as well as 3×3 HRA are projected under both healthy and faulty conditions. Mathematical modeling equations of single actuation element were solved in MATLAB/Simulink module and based on the results obtained, an iconic model of HRA with series-in-parallel configuration was modeled in Simulink/Simscape module. The simulation results are observed in open-loop and closed-loop control of actuation elements under both healthy and faulty conditions. It was observed that there is no sudden failure of actuation, but there is a graceful degradation in the performance of actuation depending upon the number of faulty elements. However, the actuator was in working condition even after three actuation elements are failed.